CHALLENGES OF DEMOCRACY AND DEVELOPMENT IN NIGERIA’S NIGER DELTA REGION: AN APPRAISAL - Gabriel Tyoyila Akwen; Daniel Terhenmen Gever (European Scientific Journal, ESJ, 2012)
The Niger Delta of Nigeria is the largest mangrove forest in Africa and the chief source of wealth to the Nigerian state. This naturally endowed region once became a hot bed of kidnapping, violence, insurgency, crude oil bunkering, gang war and hostage taking. This paper investigates the challenges of democracy and development in Nigeria.s Niger Delta region. It relied heavily on secondary data. Using the Marxist political economy approach, the paper reveals that the tensions that rob the region of its peace and stability were the people.s quest to get a reasonable share of the states resources. Since democracy and development cannot thrive under a restive atmosphere, it recommends that current measures at restoring peace and infusing a massive infrastructure in the area should be maintained. Lastly, the provision of life sustaining skills for the youths of the region should be continued. This will enable them survive without recourse to violence and criminality.